A unique case of bilateral hydronephrosis caused by a fecalith. Issue 1 (23rd November 2017) - Kulkarni, Archana; Kimoto, Maryann; Morales, Rafael; Kaura, Amit
Key Clinical Message: This is a unique case that signifies the importance to look beyond the genitourinary system for causes of hydronephrosis. In addition, we outline the manner in which a fecalith should be addressed. Abstract : This is a unique case that signifies the importance to look beyond the genitourinary system for causes of hydronephrosis. In addition, we outline the manner in which a fecalith should be addressed.